Validation study of the Malay version of the 3-minute diagnostic interview for confusion assessment method defined delirium (3D-CAM) / Chin Yi Zhe - Chin , Yi Zhe (2016)
Background: Postoperative delirium is an increasingly recognized geriatric conundrum that complicates 12-51 °'o of the elderly population after surgery. But it is often overlooked and under-diagnosed. The 3D-CAM tool, which was recently validated as a rapid instrument for identifying delirium, has the potential to empower relevant clinicians to diagnose postoperative delirium earlier for prompter interventions to improve patients• overall outcome. With the growing of populations across many nations, including those in the South-East Asia, this study aims to translate and validate the Malay version of the 3D-CAM for imminent research and clinical use. Methods: The 3D-CAM was translated and culturally adapted to the Malay version in keeping with existing guidelines on translation. Subsequently, recruited post-operative elderly patients, aged 65 and above, were separately and independently assessed for delirium by two trained anaesthetic registrars using the Malay 3D-CAM tool against the reference diagnosis by a psychiatrist using the Diagnostic and Statistical Manual of Mental Disorders V (DSM-V) to test the validity and reliability of the Malay 3D-CAM. Results: Of the II 0 recruited patients, 100 patients who met the inclusion and exclusion criteria were evaluated. They had a median age of 71 years old. Our expert panel identified 1 0°1o of these patients to have postoperative delirium. The sensitivity of the Malay 3D-CAM \\as 80% for assessor 1 and 90°'<, for assessor 2, while its specificity was 96.70t0. The Malay 3D-CAM has a near-perfect inter-rater reliability (1<=0.85. p<0.00l). Conclusion: The Malay 30-CAM demonstrated high sensitivity and specificity in identifying postoperative delirium in the elderly population compared to reference diagnosis of delirium. This translated tool could be integrated into standard of care of Malaysian post-surgical elderly patients to actively identify post-operative delirium for prompt management.